Using waist circumference as a predictor of hypertension in Manzese, Dar es Salaam: a community-based cross-sectional study, 2023 - Godbless Henry Mfuru; James N. Allan; Agnes Njau; Omary Ubuguyu; Khadija Y. Malima (BMC Public Health)
Abstract Introduction It is estimated that 1.3 billion people in the world have hypertension and a large proportion of them are unaware. Waist circumference has emerged as Potential predictor of Cardiovascular Diseases (CVD) risk; however, fewer studies in Tanzania have evaluated its role in screening for CVD risk. This study aimed to determine the role of waist circumference in screening for hypertension, a major risk for CVD. Methods An analytical cross-sectional study was conducted in Manzese ward, Dar es Salaam, from August to September 2023. Adults who attended a screening campaign were systematically randomly sampled. Data were collected using WHO STEPwise Approach to Chronic Disease Risk Factor Surveillance questionnaire. The relationship between waist circumference and hypertension was analyzed using a Modified Poisson regression model with robust standard errors. Results Among 561 participants screened, 70.4% were female, with a median age of 47 years (IQR: 34–58). The overall prevalence of hypertension was 45.8% (95% Confidence interval [CI]: 41.7–49.9). Those with elevated waist circumference had a 34% higher likelihood of hypertension (adjusted prevalence ratio [aPR] 1.34, 95% CI: 1.03–1.73, P = 0.027). Participants aged 35 and above were 160% more likely to be hypertensive (aPR 2.6, 95% CI: 1.79–3.78, P < 0.001). A family history of hypertension increased the likelihood by 31% (aPR 1.31, 95% CI: 1.08–1.59, P = 0.006).  Conclusion  This study reveals a high prevalence of hypertension among Manzese residents, with key risk factors including elevated waist circumference, age ≥ 35 years and a family history of hypertension. The strong association between waist circumference and hypertension suggests that incorporating waist measurement into cardiovascular risk assessment could enhance early detection and improve prevention efforts. This practical and cost-effective approach may improve the identification of at-risk individuals, enabling timely interventions and reducing the long-term burden of hypertension-related complications.